BALITA STUNTING DI POSYANDU DAERAH SUNGAI LAKAM BARAT WILAYAH UPT PUSKESMAS TANJUNG BALAI KARIMUN - Batubara, Saiful; Batubara, sauqi Sahrur (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2025)
Tanjung Balai Community Health Center UPT is one of the Community Health Centers on Karimun Island, and the West Lakam River Regional Posyandu is one of the Community Health Centers that is actively carrying out stunting reduction programs. The research design used is a descriptive method to describe or illustrate a characteristic that occurs in the community and collect data on characteristics related to stunting children in all West Lakam River Posyandu in the Tj.Balai Karimun Community Health Center Work Area in August - December 2023. From the results of field research, there were still significant numbers of cases of Stunting Toddlers at the Sungai Lakan Posyandu, with the characteristics of Stunting Mothers of Toddlers having low education and low economic capabilities so that it is necessary to strengthen their knowledge and economy.